2018
DOI: 10.1016/j.regsciurbeco.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Land values, property rights, and home ownership: Implications for property taxation in Peru

Abstract: published by Elsevier. It is posted here by agreement between them. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The concept of property rights is central to understanding the operations of land and real estate markets (Hawley et al, 2018;Malpezzi, 1999). Property rights are the claims or expectations that a person makes regarding the potential benefits that derive from an asset (Bromley, 1989;Paul, 2017;Schutter et al, 2019).…”
Section: Conceptual Discussion 31 Arguments For and Against Formalisation Of Property Rightsmentioning
confidence: 99%
“…The concept of property rights is central to understanding the operations of land and real estate markets (Hawley et al, 2018;Malpezzi, 1999). Property rights are the claims or expectations that a person makes regarding the potential benefits that derive from an asset (Bromley, 1989;Paul, 2017;Schutter et al, 2019).…”
Section: Conceptual Discussion 31 Arguments For and Against Formalisation Of Property Rightsmentioning
confidence: 99%
“…Pajak properti mempunyai pengaruh heterogenitas terhadap lingkungan dimana lingkungan tersebut akan memberikan pengaruh atas perubahan beban pajaknya untuk setiap kelas properti, seperti pemilik tanah kosong menanggung beban beban, tetapi dampak terhadap pemilik tanah yang dikembangkan beragam di berbagai SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi) lingkungan (Cohen & Fedele, 2017). Kondisi di Amerika Latin bahwa permintaan barang publik sangat tinggi, namun kondisi pendapatan negara setempat sangat rendah yang menyebabkan keterbatasan dalam pembiayaan hal ini disebabkan karena nilai tanah dari pemilik properti lokal meningkat namun hasilnya tidak diperoleh secara efisien melalui sistem pajak properti ketika pasar informal ada sehingga kurang maksimalnya penggalian potensi atas pajak properti (Hawley et al, 2018). Berdasarkan survei yang dilakukan oleh Goytia dan Cristini (2017) diperoleh hasil yang menunjukan bahwa beberapa kota di Argentina seperti Chaco, Corrientes, dan Chubut, lebih suka memutakhirkan data pertanahan (kadaster) untuk meningkatkan pendapatan pajak sementara yang lain telah mereformasi tarif pajak.…”
Section: Pajak Bumi Dan Bangunanunclassified
“…Fisher and Quayyum (2006) described homeownership as broadly associated with socioeconomic factors and concluded that it significantly influences the desire to acquire a house. Hawley et al (2018) argued that land values (economic factors) and property rights have a more significant association with homeownership because every homeownership factor has economic or financial implications. These social, economic, and environmental factors and their elements such as family ties (Cheung et al, 2020), sense of place and belief does influence the decision to own a house or not.…”
Section: Introductionmentioning
confidence: 99%